Synthesis and Characterization of TiAl‐Based Nanocomposites by a Melt Electromagnetic Stirring Process1. Issue 10 (21st April 2015) - Zhang, Zhiyong; Wang, Yanli; Xu, Xiangjun; Liang, Yongfeng; Zhang, Laiqi; Lin, Junpin
<x xml:space="preserve">Abstract</x> Ceramic nanoparticles were considered difficult to be dispersed well in liquid metal, especially in non‐reactive systems, by stir mixing methods due to their high specific surface energy. In this paper, an electromagnetic stirring process was exploited to disperse ceramic nanoparticles in an active TiAl alloy melt. The results indicate that finely dispersed nanoparticles can be obtained by stir mixing with the aid of reactive wetting. The presence of nanoparticles during solidification can refine the primary dendrites dramatically, which was primarily determined by the extent of particle pushing at the liquid–solid interface. Among the studied particles, TiC can refine the (γ + α2) lamellar colonies, which is attributed to the dissolution of carbon and subsequent precipitation of Ti2AlC during L + β → β + α. The Vickers hardness of the nanocomposites as a function of stirring time was tested, and the Ti–45Al/TiC nanocomposite produced by 10 min stir mixing has the highest value, measuring 450 HV.